PHARMACOLOGICAL IMPACT OF RUTIN AND QUERCETIN IN ALCOHOL-INDUCED NEUROPATHY IN RATS - PRASHANT S KUMBHAR; SONALI MANWATKAR; BIMLESH KUMAR; SAMRUDDHI BHIKAJI RAJE; AKANKSHA SUNIL CHAVAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The purpose of this research study was to assess the effect for the simultaneous administration of quercetin and rutin and their combination in neuropathic pain (NP) caused by alcohol. Methods: Rats were given ethanol (35% v/v, 10 g/kg, p.o.) for 10 weeks to induce alcoholic NP. Ingested Rutin (100 and 50 mg/kg, p.o.) and Quercetin (40 and 20 mg/kg, p.o.) individually and at their lower doses in combination (50 mg/kg Rutin and 20 mg/kg Quercetin, p.o.) to examine differences in mechanical and thermal hyperalgesia, allodynia, and histopathological parameters. Biochemical measurements of glutathione, thiobarbituric acid reactive species, and protein are used to assess the oxidative stress in alcoholic neuropathy. Results: The results of the study demonstrated that rats given alcohol for 10 weeks experienced severe mechanical and thermal hyperalgesia, allodynia, and an increased degree of oxidative stress. Lower and greater dosages of both medications alone were used to reduce the symptoms of NP brought on by alcohol. However, simultaneous low-dosage treatment of quercetin and rutin has been proven to significantly improve neurological, histopathological, and metabolic functions when compared to their individual administration. Histopathological studies, which show that nerve regeneration occurs, have provided strong support for the treatment of NP. Conclusion: Therefore, it is hypothesized that giving quercetin and rutin at the same time may help reduce NP and offer an alternate therapeutic strategy.